A Study the Role of School Administrator on Internal Supervision under Nakhon Ratchasima Primary Educational Service Area Office 5 - ป้องญาติ, วิไลลักษณ์; ภูมิโคกรักษ์, ประหยัด (Ratchaphruek Journal, 2018)
The purposes of this research were to study the role of school administrators on internal supervision, to compare the role of school administrators on internal supervision and to analyze schools’ sizes and to promote to the role of school administrators on internal supervision under Nakhon Ratchasima Primary educational Service Area office 5. The sampling group was 140 schools under Nakhon Ratchasima primary educational service area office 5 by stratified random sampling. The instruments for data collection were a questionnaire analyzed to find mean and standard deviation while variance was analyzed with F-test and structured interview was analyzed with frequency distribution, percentage and descriptive statistics. The findings revealed that. 1. Role of supervisory of educational institution administrators in overall were at a high level. Morale creation and encouragement of teachers were the highest followed by suggestion on in-house operation and teacher development respectively. 2. Comparing role of supervisory performance of education institution administrators by school size in overall, the researcher found it different. When considering by aspect, the results indicated that they were distinct with statistical significance at .05. 3. Creating guidelines of promoting supervisory performance role of educational institution administrators, the researcher considered results of investigating approaches of promoting supervisory performance role of the educational institution administrators by school size as follows For small size school, should arrange a meeting with teacher along with educational institution committee and community to manage resources in developing curriculum properly. Furthermore, there should be monitoring, evaluating and assessing learners in order to evaluate curriculum quality. A quality library should be established; such as, e-learning in learning should be promoted with various processes i.e. teaching in mixed classes, implementing ICT for learning. For middle size school, should allocate budgets by head of students in order to purchase materials and equipment for curriculum development. Moreover, there should be suggestion on instructional activities to be consistent with indicators of the curriculum and allocation of budget for teachers in each proposed program or activity. Plus, personnel should be development to have knowledge and to understand about instructional skills. For large size school, the administrators should promote teachers to participate in development the curriculum and its implementation which should be conducted under curriculum framework. Additionally, there should be monitoring results periodically, giving advices when teachers have problems from implementing the curriculum, and determining the policy about purchasing or developing library, equipment and tools, laboratory, and workshop inside the educational institution. Finally, activities should be arranged according to the central policy with systematic assessment and analysis of supervisory performance.